Relacje międzykulturowe, globalna ekumena, kulturowa różnorodność - Adam Nobis (Ksiegarnia Akademicka Publishing, 2017)
Intercultural Relations, Global Oecumene, Cultural Diversity The classical anthropological paradigm of plurality of separate cultures became contested at the turn of the last century. Researchers such as Thomas Hylland Eriksen, Wolfgang Welsch or Ulf Hannerz show that there are no intercultural boundaries anymore and cultures permeate within each other. Some of the researchers suggest that we can speak only about a single global culture. The outlined vision of reality pressures us to ask the old question of cultural studies: What are the cultural differences and where are their sources? It leads us to another issue: How should we understand intercultural relations if we accept the axiom of the single culture? The article is an attempt to deal with those problems.